Translation, cultural adaptation and validation of the SCHNOS in French - Marie-Renée Atallah; Daniel Milad; Youcef-Hamza Benamer; Mikhail Saltychev; Sam P. Most; Sami P. Moubayed (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS) is a validated questionnaire that assesses functional and aesthetic outcomes of rhinoplasty patients. There are 274 million French speakers worldwide, and this questionnaire is currently not available in French. The purpose of this study was to translate, adapt, and validate a French version of the SCHNOS questionnaire. Methods The SCHNOS questionnaire was translated from English to French according to international guidelines. Ten French-speaking rhinoplasty patients were interviewed in order to evaluate the understandability and acceptability of the translation and produce a final version. The final version was administered prospectively to 25 rhinoplasty patients and 25 controls at two-week intervals. It was then administered to 165 consecutive patients. Psychometric properties were evaluated using the Item Reponse Theory (IRT) and confirmatory factor analysis (CFA). Results Three items from the original SCHNOS were modified to produce the French-SCHNOS (F-SCHNOS). Discrimination abilities of F-SCHNOS-O and F-SCHNOS-C were perfect, with values of 2.18(p < 0.001, 95% CI 1.74 to 2.62) for SCHNOS-O and 2.62(p < 0.001, 95% CI 2.03 to 3.21). Internal consistency was high, with Cronbach’s alpha of 0.93 for F-SCHNOS-O and 0.95 for F-SCHNOS-C. IRT showed good psychometric properties with almost each step up or down across the scale associating with meaningful differences in outcome severity. All four SCHNOS-O items were equally “important” in defining the total score. The F-SCHNOS-C total score was defined by mostly four out of six items. Conclusions The SCHNOS was translated, adapted, and psychometrically validated for use in a French-speaking population.